Randomized Controlled Trial of Adjuvanted Versus Nonadjuvanted Influenza Vaccine in Kidney Transplant Recipients. Issue 3 (March 2016) - Kumar, Deepali; Campbell, Patricia; Hoschler, Katja; Hidalgo, Luis; Al-Dabbagh, Mona; Wilson, Leticia; Humar, Atul
Abstract : Background: Influenza vaccine containing an oil-in-water emulsion adjuvant (MF-59) may lead to greater immunogenicity in organ transplant recipients. However, alloimmunization may be a concern with adjuvanted vaccines. Methods: We conducted a randomized trial comparing the safety and immunogenicity of adjuvanted versus nonadjuvanted influenza vaccine in adult kidney transplant patients. Patients were randomized 1:1 to receive 2012 to 2013 influenza vaccine with or without MF59 adjuvant. Preimmunization and postimmunization sera underwent strain-specific hemagglutination inhibition assay. HLA alloantibody was determined by Luminex single-antigen bead assay. Results: We randomized 68 patients and 60 (29 nonadjuvanted; 31 adjuvanted) had complete samples available at follow-up. Seroconversion to at least 1 of 3 influenza antigens was present in 71.0% versus 55.2% in adjuvanted versus nonadjuvanted vaccine respectively ( P = 0.21). Geometric mean titers and seroprotection rates were similar between groups. Seroconversion rates were especially low in those on MMF of 2 g or greater daily (44.4% vs 71.4%; P = 0.047). In the subgroup of patients 18 to 64 years old, seroconversion was significantly greater with adjuvanted vaccine (odds ratio, 6.10; 95% confidence interval, 1.25-28.6). There were no increases in HLA alloantibodies in patients who received adjuvanted vaccine. Conclusions: Adjuvanted vaccine was safe and had similar immunogenicity to standard vaccine in the overall transplant cohort but did show a potential immunogenicity benefit for the 18 to 64 years age group. Abstract : This randomized trial of adjuvanted versus nonadjuvanted influenza vaccine in adult kidney transplant patients showed that the odds ratio for seroconversion among those 18Y64 was 6.10 with the adjuvanted vaccine. No one developed HLA sensitization by single antigen bead testing.